2018
DOI: 10.1016/j.hemonc.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The relation between protein Z polymorphism and the risk of thrombosis in Egyptian patients with antiphospholipid syndrome

Abstract: Protein Z-79 G/A gene polymorphism may be of a protective value against thrombosis in APS. The G79A polymorphism of protein Z was not found to be an independent risk factor of thrombosis in APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For the diagnosis of TAPS, Yomna K et al found that protein Z-79 G/A gene polymorphism could prevent APS thrombosis (68). Plasin Rodriguez et al also tested PROCR, the gene encoding endothelial cell protein C receptor.…”
Section: Differential Diagnosis Of Aps Subtypesmentioning
confidence: 99%
“…For the diagnosis of TAPS, Yomna K et al found that protein Z-79 G/A gene polymorphism could prevent APS thrombosis (68). Plasin Rodriguez et al also tested PROCR, the gene encoding endothelial cell protein C receptor.…”
Section: Differential Diagnosis Of Aps Subtypesmentioning
confidence: 99%